The Efficacy of Antifungal Medications and Plant Extracts Against Candida albicans Isolated from Vulvovaginitis Women - Abdulla, Nareen Qadr Faqe; Ismael, Hero M. (Iraqi Journal of Science, 2023)
Fungus Candida spp. causes vulvovaginal candidiasis (VVC) which is a fungal infection of the genital mucosa. This investigation was on the isolation of Candida albicans from cervical-vulvovaginal patients in Erbil hospitals, Kurdistan region, Iraq and its identification is done using phenotypic and molecular approaches. Then biofilm production was detected through phenotypic tests such as Congo red agar (CRA) and disclosure virulence genes, agglutinin-like sequence(ALS1) and hyphal wall protein (HWP1). The susceptibilities of antifungal medications and plant extracts against C. albicans isolates were then assessed. This study showed low susceptibilities values to all tested antifungals such as econazole (12mm), miconazole (12mm) and nystatin (14mm) in the disc diffusion method with the exception of ketoconazole (20mm) which had high susceptibilities values. In this research each ethanol pomegranates peel extracts (EPPE) (200mg/ml), aquatic pomegranates peel extracts (APPE) (200mg/ml) and pomegranate molasses (PM) were used. In the agar well diffusion method, C. albicans showed low susceptibilities values against (PM) (8mm). However, it showed high susceptibilities values against (EPPE) (18mm) when compared to each of the antifungal agents: econazole, miconazole and nystatin. Results of the study showed that pomegranate peel could be new therapeutic promisingekey ingredient in antifungal medications development. It is an alternate antifungal medication which is useful for C. albicans treatment.